Gambaran Celebrity Worship pada Dewasa Awal di Jakarta - Widjaja, Annisa Kusuma; Ali, Moondore Madalina (Bina Nusantara University, 2015)
The intensity of celebrity worship is increasingly occurring in Indonesia. Celebrity worship is any form of behavior or feelings that arise from inner to worship an idol figure as a gratification, entertainment, or to fill in the emptiness. Celebrity worship is divided into entertainment social, intense personal, and borderline pathological. Celebrity worship can be done by anyone and its intensity decreases with age. However, some media reports that celebrity worship is found in early adulthood. Thus the purpose of this study was to describe behavior of celebrity worship in early adulthood aged 20-30-year-old in Jakarta. The research design is quantitative descriptive method. Subjects in this study amounted to 250 people who live in Jakarta. It is found that 34% (85 people) into the Entertainment Social levels, 34.8% (87 people) into the level Intense Personal, and 31.2% (78 people) into the Borderline Pathological levels. It shows that celebrity worships still exist in early adulthood in Jakarta.